Ab initio calculations and experimental study of piezoelectric YxIn1−xN thin films deposited using reactive magnetron sputter epitaxy. (15th February 2016) - Tholander, C.; Birch, J.; Tasnádi, F.; Hultman, L.; Palisaitis, J.; Persson, P.O.Å.; Jensen, J.; Sandström, P.; Alling, B.; Žukauskaitė, A.
Abstract: By combining theoretical prediction and experimental verification we investigate the piezoelectric properties of yttrium indium nitride (Y x In1− x N). Ab initio calculations show that the Y x In1− x N wurtzite phase is lowest in energy among relevant alloy structures for 0≤ x ≤0.5. Reactive magnetron sputter epitaxy was used to prepare thin films with Y content up to x =0.51. The composition dependence of the lattice parameters observed in the grown films is in agreement with that predicted by the theoretical calculations confirming the possibility to synthesize a wurtzite solid solution. An AlN buffer layer greatly improves the crystalline quality and surface morphology of subsequently grown Y x In1− x N films. The piezoelectric response in films with x =0.09 and x =0.14 is observed using piezoresponse force microscopy. Theoretical calculations of the piezoelectric properties predict Y x In1− x N to have comparable piezoelectric properties to Sc x Al1− x N. Graphical abstract: